The Vroman I Site (NYSM# 10146 and 10148): A Transitional/Early Woodland Camp in the Town of Schoharie, Schoharie County, New York - C. B. Rieth (The Bulletin: Journal of the New York State Archaeological Association, 2016)
The Vrooman I site consists of a small Transitional/Early Woodland campsite located near the confluence of the Fox and Schoharie creeks in the Town of Schoharie, Schoharie County, New York. The site produced a small concentration of chert flakes, broken bifaces, a broken (Woodland) projective point, and small expedient tools. The absence of features reinforces the site's tentative nature. Comparisons with contemporaneous sites in eastern New York place the site within a larger regional seetlement and interaction system.